State-of-the-Art Research in Biomolecular Crystals - Moreno, Abel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on different techniques and strategies to obtain high-quality crystalline structures of biological macromolecules via X-ray diffraction and synchrotron radiation. Contributions cover various aspects ranging from the fundamentals of crystal growth of biomolecules with biomedical applications and materials science through to the biotechnological applications of crystals.